Co-production of a CArdiac Brief INtervention (CABIN) for patients prior to discharge following acute myocardial infarction (AMI). (2nd July 2022) - Caughers, G; Wilson, A; Donnelly, P; Bradley, J; Fitzsimons, D
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Public Health Agency Northern Ireland, Research and Development PhD Fellowship Background: Recovery from AMI can be challenging for patients without adequate psychosocial support to overcome anxiety, address misconceptions and initiate lifestyle change (1, 2). Reduced length of stay has minimised the opportunity for nurses to evaluate patients' holistic needs and initiate effective in-hospital interventions (3). Patients and nurses discussed these challenges openly and worked together in this co-design study to develop a brief intervention for the pre-discharge period. Method: A multi-site, co-design project was conducted with an exploratory phase of interviewing and focus groups with patients and staff involved in CR. The data from this exploratory phase informed a series of working-group meetings during which this intervention was developed. Results: The CABIN (CArdiac Brief INtervention) offers brief, reassuring and compassionate discussions alongside educational content. CABIN consists of 8 components as seen in figure 1. It is designed to be used by nursing staff in the acute setting with patients following their AMI. Staff delivering the intervention must have full understanding of the local CR programme to offer practical advice if necessary. Conclusion: CABIN provides a tangible means to emotionally support patients in the acute phase of recovery following AMI. It is envisaged that CABIN will empower acute clinical nursing staff to address the emotional needs of patients in a way which will encourage attendance at CR and subsequent recovery.